2008
DOI: 10.1016/j.neuropharm.2008.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ectodomain and transmembrane regions in ethanol and agonist action in purinergic P2X2 and P2X3 receptors

Abstract: SUMMARYThe present work investigated sites of ethanol action in ATP-gated P2X receptors (P2XRs) using chimeric strategies that exploited the differences in ethanol response between P2X2R (inhibition) and P2X3R (potentiation). We tested ethanol (10-200mM) effects on ATP-and α,β-methylene-ATP (α,β-meATP)-induced currents in wildtype P2X2, P2X3 and chimeric P2X2/P2X3Rs expressed in Xenopus oocytes using two-electrode voltage-clamp (−70mV). Exchanging ectodomain regions of P2X2 and P2X3Rs reversed wildtype ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Previous investigations suggest that the interface between the ectodomain and the TM segments in P2X4Rs contains targets for ethanol and IVM action or modulation [17,23,24]. We have identified residues Asp331 and Met336 in the ectodomain-TM2 segment interface to be important for ethanol modulation, whereas residues Asn338, Ser341, Gly342, Leu346, Gly347, Ala349, and Ile356 in the TM2 segment were found to play a role in IVM modulation of the receptor [25,26].…”
Section: Introductionmentioning
confidence: 71%
“…Previous investigations suggest that the interface between the ectodomain and the TM segments in P2X4Rs contains targets for ethanol and IVM action or modulation [17,23,24]. We have identified residues Asp331 and Met336 in the ectodomain-TM2 segment interface to be important for ethanol modulation, whereas residues Asn338, Ser341, Gly342, Leu346, Gly347, Ala349, and Ile356 in the TM2 segment were found to play a role in IVM modulation of the receptor [25,26].…”
Section: Introductionmentioning
confidence: 71%
“…ATP is a full agonist for rP2X3R with estimated EC 50 values of 1.2 M (Chen et al, 1995), 2.6 M (Pratt et al, 2005), 4.1 M (Asatryan et al, 2008), and 7.3 M (Grote et al, 2005), but the precision of these estimates is limited by profound desensitization (Khmyz et al, 2008). Similar to the rP2X1R, ␣␤-meATP is a full agonist at rP2X3R, acting with a potency similar to (Pratt et al, 2005;Asatryan et al, 2008) or slightly lower than (Chen et al, 1995) that of ATP. 2-meSATP is also a full agonist for this receptor, whereas ATP␥S acts as a partial agonist Liu et al, 2001a).…”
Section: Activation and Regulation Of P2xrsmentioning
confidence: 97%
“…In another study, His 241 was identified as a residue responsible for the ethanol sensitivity of P2X4Rs (Xiong et al, 2005). Experiments with chimeric P2X2R and P2X3R revealed that ectodomain segments at the TM interfaces play key roles in determining the qualitative and quantitative responses to ethanol (Asatryan et al, 2008). Further experiments by the same group identified Asp 331 and Met 336 as critical TM residues for the ethanol sensitivity of P2X4R .…”
mentioning
confidence: 96%
“…Two-electrode voltage-clamp recordings of oocytes were performed with an oocyte clamp amplifier (model OC-725C; Warner Instruments, Hamden, CT) using procedures published previously (Asatryan et al, 2008;Popova et al, 2010).…”
Section: Isolation Of Xenopus Laevis Oocytes and Crna Injectionsmentioning
confidence: 99%
“…Previous studies found that residues contained within the ectodomain-TM segment interfaces are important for ethanol ac-tion in P2X3Rs (Asatryan et al, 2008). Extending the investigation to P2X4Rs resulted in the identification of two key residues in the TM2 segment near the ectodomain interface (Asp331 and Met336) that, when substituted to alanine, caused a significant reduction in ethanol (10 -200 mM) inhibition of ATP-gated currents (Popova et al, 2010).…”
Section: Introductionmentioning
confidence: 95%